Implementing Systems Engineering in the Civil Engineering Consulting Firm: An Evaluation. Issue 1 (19th February 2016) - de Graaf, Robin; Voordijk, Hans; van den Heuvel, Len
ABSTRACT: This study explores the challenges that civil engineering consulting firms face in their projects when they apply Systems Engineering (SE). It is also explained were these firms should focus when improving the use of SE. To conduct this study, the methodology of Eisenhardt (Building theories from case study research, Acad Manage Rev 14 [1989], 532–550) for building theory from case study research is used. The extent, to which SE is applied, is assessed in six civil engineering projects, using a newly developed framework containing an extensive list of questions about how and why SE was applied. Based on this assessment, it is shown that there are three major reasons why SE was not applied to the full extent. First, SE procedures and responsibilities were not always clearly established and communicated to team members. Second, team members were in a learning process and did not yet possess all the SE knowledge and skills required. Finally, there was a lack of a demanding client to enforce the use of SE. This paper also presents recommendations for improving the application of SE in projects, related to methods, skills, and the client. Further research should focus on different (kinds of) companies within the civil engineering industry.